Expression of Haemagglutinin-Neuraminidase Envelope Protein of Newcastle Disease Virus Strain Af2240 in Centella Asiatica (Pegaga) Embryogenic Calli Through Optimized Particle Bombardment Method - Lai, Kok Song (2008)
Centella asiatica is a locally important medicinal plant. It is non-toxic, high in medicinal values, and can serve as a good candidate for genetic manipulation. However, to date no transformation protocol has been developed to fully utilize the potential of this plant. Therefore, this research is to establish an efficient particle bombardment transformation protocol for C. asiatica embryogenic calli. In addition, an attempt to express the haemagglutinin-neuraminidase (HN) protein from Newcastle disease virus (NDV) strain AF2240 in C. asiatica embryogenic calli were carried out using the developed transformation system. The HN protein can serve as a potential vaccine candidate for Newcastle disease (ND) in poultry. The induced embryogenic calli revealed the presence of extracellular matrix layer (ECM) during the microscopy studies. Particle bombardment transformation protocol was developed using the green fluorescent protein (GFP) as reporter. A total of eight parameters mainly different target distance, helium pressure, gold particles size, chamber vacuum pressure, number of bombardment, precipitation agents, post-bombardment incubation time, and plasmid DNA concentration were identified and successfully optimized. Based on the established protocol, transformations of C. asiatica embryogenic calli were performed using the constructed recombinant pMDC32’HN and HBT95:sGFP(S65T)-NOS’HN plasmids. Genomic PCR analysis revealed the presence of HN transgene in the transformed lines. Unfortunately no protein bands were detected during SDS-PAGE and western blotting, indicating low or no HN protein expression. Transformation using recombinant HBT95:sGFP(S65T)-NOS’HN plasmid resulted in very low GFP expression as compared to the positive control. Nonetheless, the mRNA transcripts were detected in the RT-PCR analysis. Positive signal from the dot blot assay further confirmed the presence of the HN protein expression in the transformed lines.